Inappropriate Antibiotic Use in Zimbabwe in the COVID-19 Era: A Perfect Recipe for Antimicrobial Resistance - Itai Chitungo; Tafadzwa Dzinamarira; Tinashe K. Nyazika; Helena Herrera; Godfrey Musuka; Grant Murewanhema (Antibiotics, 2022)
The global COVID-19 pandemic has resulted in an upsurge in antimicrobial use. The increase in use is multifactorial, and is particularly related to the empirical treatment of SARS-CoV-2 and suspected coinfections with antimicrobials and the limited quality of diagnostics to differentiate viral and bacterial pneumonia. The lack of clear clinical guidelines across a wide range of settings, and the inadequacy of public health sectors in many countries, have contributed to this pattern. The increased use of antimicrobials has the potential to increase incidences of antimicrobial resistance, especially in low-resource countries such as Zimbabwe already grappling with multidrug-resistant micro-organism strains. By adopting the antimicrobial stewardship principles of the correct prescription and optimised use of antimicrobials, as well as diagnostic stewardship, revamping regulatory oversight of antimicrobial surveillance may help limit the occurrence of antimicrobial resistance during this pandemic.